Mechanosensory structures in the beaks of probe-foraging birds in relation to their foraging ecology - du Toit, Carla J (Department of Biological Sciences, 2022)
Some taxa of probe-foraging birds (ibises, kiwi and scolopacid shorebirds) possess the sensory of capability of “remote-touch”, allowing them to detect mechanical vibrations in their foraging substrates using a specialised bill-tip organ in their beaks. This enables them to remotely detect the location of prey submerged in opaque substrates in the absence of all other sensory cues. The bill-tip organ that facilitates remote-touch is made up of mechanoreceptors housed in dense clusters of foramina in the distal portions of the beak bones (each unit of foramen and associated receptors is referred to as a “sensory pit”). Previous research showed that in ibises (Family: Threskiornithidae), species which live in more aquatic habitats tend to have more extensively pitted beak bones (i.e., the relative size of the bill-tip organ increases with increasing aquatic habitat usage of the species) than species living in drier habitats. The first three data chapters of this thesis investigate this trend, using three species of southern African ibises. These three species represent a spectrum of habitat usage, ranging from mainly terrestrial (Hadeda Ibises) to mainly aquatic (Glossy Ibises), with African Sacred Ibises a generalist species. My main hypothesis is that the interspecific differences in bill-tip organ morphology are related to differences in the moisture content of the birds' foraging substrates, as this affects how well these substrates transmit vibrations that the birds are sensing using remote-touch. The morphology of the bill-tip organs of the three species (Chapter 2) and their foraging behaviour in the wild (Chapter 3) indicate that species which forage in less saturated substrates have higher densities of mechanoreceptors in their bill-tip organs, suggesting that they are more sensitive to vibratory cues. This follows logically from the fact that drier substrates transmit vibrations more poorly than wetter ones, thus I hypothesize that species which forage frequently in dry substrates may have faced evolutionary pressure selecting for more sensitive bill-tip organs. My data on foraging behaviour of all three species of ibis in the wild suggests that bill-tip organ pitting extent on the beak bones is linked to depth of probing, which is in turn related to the penetrability of their probing substrates. As substrate penetrability is strongly affected by moisture content, the extent of pitting on the bill-tip organ is a good osteological correlate for the water content of the foraging substrate in the absence of soft tissue histology in ibises. Experiments using captive Hadeda Ibises (Chapter 4) provide further support for the hypothesis that species foraging in drier substrates require more sensitive bill-tip organs as their success rate using remote-touch was positively affected by substrate moisture content. Additionally, as this species' recent range expansion across southern Africa has been closely tied to increased soil irrigation in urban and agricultural habitats, I suggest that this in part due to Hadeda Ibises being better able to detect prey in more saturated substrates. The final data chapter of this thesis concerns the evolution of the remote-touch bill-tip organ in modern birds: the three families which possess remote-touch capability are widely phylogenetically separated, indicating that it evolved convergently. Kiwi (order: Apterygiformes) present an interesting case, as they are part of the palaeognath clade of Neornithes and are the only members of this clade which use remote-touch probeforaging. However, various other palaeognathous birds (ostriches & emu) possess a bill-tip organ, though its function in these taxa is unknown. I show that all species of modern palaeognathous birds (including the extinct moa and elephant birds) have the same beak morphology (bony pits containing numerous mechanoreceptors). This is at odds with the fact that none use the organ or possess the neuroanatomical correlates that would allow them to do so, indicating that the organ is vestigial in most palaeognaths. I thus hypothesized that the trait is plesiomorphic in palaeognathous birds, inherited from a common ancestor that used remote-touch probe-foraging. As the bill-tip organ is characterized by pitting in the beak bones, I was able to study the fossilized beaks of the oldest known palaeognaths, the lithornithids (which evolved during the Cretaceous period). By comparing them to an extensive sample of extant birds' beak bones, I showed that these ancient palaeognaths had bill-tip organs which were probably capable of remote-touch. Aside from supporting the hypothesis that the remote-touch bill-tip organ in palaeognaths is plesiomorphic, this indicates that remote-touch is one of the oldest documented foraging specialisations in modern birds.